2004
DOI: 10.1161/01.hyp.0000111833.82664.0c
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Reduction in Estrogen Receptor–Mediated Mechanisms of Vascular Relaxation in Female Spontaneously Hypertensive Rats

Abstract: Abstract-Hypertension increases with aging, and changes in vascular estrogen receptors (ERs) may play a role in age-related hypertension in women. We tested whether age-related increases in blood pressure in female spontaneously hypertensive rats (SHRs) are associated with reduction in amount and/or vascular relaxation effects of estrogen and ER. Arterial pressure and plasma estradiol were measured in adult (12 weeks) and aging (16 months) female SHRs, and thoracic aorta was isolated for measurement of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 54 publications
5
47
2
1
Order By: Relevance
“…This contrasts previous studies which demonstrated physiological concentrations of 17β-estradiol reduced the constrictive response to ET-1 in market-age pigs (Sudhir et al, 1997;Teoh et al, 1999). However, Wynne et al (2004) similarly found that advanced age decreases the inhibitory effect of 17β-estradiol on calcium influx.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts previous studies which demonstrated physiological concentrations of 17β-estradiol reduced the constrictive response to ET-1 in market-age pigs (Sudhir et al, 1997;Teoh et al, 1999). However, Wynne et al (2004) similarly found that advanced age decreases the inhibitory effect of 17β-estradiol on calcium influx.…”
Section: Discussioncontrasting
confidence: 99%
“…24 An alternative ex- planation for the absence of estrogen-induced vasodilation in HCAs, at least in women, is the change in estrogen receptor cellular localization during perimenopause. 25 Furthermore, estrogen inactivates reactive oxygen species like the vasodilator H 2 O 2 26,27 and alters the AT 1 /AT 2 receptor ratio. 28,29 Both phenomena will directly affect Ang II-induced vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Others, conversely, have described significant effects of aging on vascular function in middle aged female rats with risk for cardiovascular disease (Fortepiani et al, 2003;Wynne et al, 2004). However, the fact that those animal models normally display increased risk for cardiovascular disease at early stage, when they are young adults, they may not represent a good model to determine aging-and menopause-associated vascular modifications in women.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%